Post-traumatic Stress Symptoms in Adolescents Exposed to the Earthquake in Lombok, Indonesia: Prevalence and Association With Maladaptive Trauma-Related Cognition and Resilience - Wahab, Suzaily; Yong, Li Ling; Chieng, Wei Keong; Yamil, Myristica; Sawal, Noor Azah; Abdullah, Nurul Qiyaam; Muhdisin Noor, Cyntiya Rahmawati; Wd Wiredarma, Siti Mardiyah; Ismail, Rosnah; Othman, Aisya Hanim; Damanhuri, Hanafi Ahmad (Frontiers in Psychiatry, 2021)
Background: Natural disasters may physically and psychologically affect an individual and its surrounding community. This study was conducted to determine the prevalence of post-traumatic stress (PTS) symptoms and its association with maladaptive trauma-related cognition and resilience among adolescents post-earthquake. Materials and methods: In this cross-sectional study, the data were collected during an intervention programme post-earthquake organized in Lombok, Indonesia involving students from the age of 14 to 19 in a state high school. Purposive sampling method was used. The questionnaires used were Children’s Revised Impact of Event Scale-13 (CRIES-13), Child Post-Traumatic Cognitions Inventory (CPTCI) and Child and Youth Resilience Measure-Revised (CYRM-R) to measure PTS symptoms, maladaptive trauma-related cognition and resilience, respectively. Results: The prevalence of PTS symptoms was 69.9%. Among the respondents, 61.37% were female and 56.48% had mothers with lower educational levels. Using multiple linear regression, the final predictors of PTS symptoms were excessive reactions (e.g., wailing loudly, miserable shrieking) of proxy during earthquake (β = 3.283, p = 0.005), maladaptive trauma-related cognition (β = 0.224, p = 0.002) and resilience (β = 0.192, p < 0.001) with female gender (β = 7.350, p < 0.001) as controlled variable. Victims who witnessed injury or death during earthquake (p = 0.003), had a proxy died during earthquake (p = 0.01) and victims who were trapped or had difficult escape (p = 0.01), also potentially predicted the occurrence of PTS symptoms, warranting further study in future. Conclusion: The presence of excessive proxy reactions during earthquake, maladaptive trauma-related cognition and resilience in adolescents exposed to the natural disaster are worth targeting and prioritized in future post-disaster interventions to reduce trauma.